Managing project risks - Edwards, Peter J. (Peter John), 1940-; Vaz Serra, Paulo, 1966-; Edwards, Michael, 1969- (Hoboken, NJ : Wiley-Blackwell, 2019)
'This book provides a comprehensive overview of project risk management. Besides offering an easy to follow but systematic approach to project risk management, the book introduces topics which have an important bearing on how risks are managed but are generally not found in other books, including risk knowledge management; cultural risk-shaping; project complexity; political risks and strategic risk management. It aims to: Effectively communicate a conceptual and philosophical understanding of risk; Establish the nature of projects and the stakeholders involved in them; Present a systematic and logically progressive approach to the processes of project risk management; Discover the drivers of project risks and the factors which shape them; Emphasise the importance of capturing and exploiting project risk knowledge; Provide guidance about implementing and building (or improving) project risk management systems in organisations'--
An overview of risk -- Projects and project stakeholders -- Project risk management systems -- Project risk contexts and drivers -- Approaches to risk identification -- Project risk identification tools -- Project risk analysis and evaluation -- Risk response and treatment options -- Risk monitoring and control -- Project risk knowledge management -- Cultural shaping of risk -- Project complexity and risk -- Political risk -- Opportunity risk management -- Strategic risk management -- Planning, building and maturing project risk management systems -- Computer applications -- Communicating risk.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Risk management; Project management; Electronic books